There's No Reason for It, It's Just Our Policy - Evans, Robert G. (Longwoods Publishing, 2009)
On June 1, 2009 the town of McAllen, Texas rose to brief prominence on the American political stage. With the highest (bar Miami) per-beneficiary costs in the entire US Medicare program, it was featured in an essay in The New Yorker by Atul Gawande, then seized upon by President Obama: “This is what we have to fix.” Behind the headlines were decades of documentation of clinical practice and analysis of regional variations by John Wennberg, Elliott Fisher and their colleagues, and by Leslie and Noralou Roos and theirs. The implications for health systems were grasped over 30 years ago and have been confirmed by more recent work. Efforts to understand these variations within standard economic theory have, however, had limited success.